Transcription of α‐glucoside transport and metabolism genes in the hybrid brewing yeast Saccharomyces pastorianus with respect to gene provenance and fermentation temperature. Issue 1 (6th June 2013) - Gibson, B. R.; Londesborough, J.; Rautio, J.; Mattinen, L.; Vidgren, V.
Abstract : The hybrid lager yeast Saccharomyces pastorianus ( S . cerevisiae × S . eubayanus ) contains several genes encoding proteins responsible for the uptake and metabolism of maltose and maltotriose. In many cases the genes occur as orthologues, that is, the S . cerevisiae gene exists along with the S . eubayanus gene. Prior to formation of the hybrid, these genes existed in organisms, which had been separated for tens of millions of years and were expected to show some level of genetic and functional differentiation. In this study, oligonucleotide probes were designed for TRAC analysis of transcription of the S . cerevisiae and S . eubayanus orthologues of AGT1, MALx1, MALx2 and MALx3 as well as the S . cerevisiae ‐derived MPH2 / 3 genes within the S . pastorianus genome. Specificity of probes was validated using mRNA from S . cerevisiae and from S . eubayanus . Probes were used to analyse gene expression during 15°P wort fermentations conducted at different temperatures (10–20°C). As well as differential expression of different genes, differential expression of orthologues was also observed during fermentation. The differences suggest that, where two forms of the gene exist, either one will dominate (as with AGT1 ) or expression will be staggered ( MALx2 ), possibly to maximize transport and for efficient degradation of sugars. Copyright © 2013 The Institute of Brewing & Distilling.